Comparative studies of segmentation techniques for breast cancer dectection - Hla Thazin Myint. (2008)
In this project, a program has been written in Microsoft Visual C++ to investigate the possibility of using image processing techniques to aid the early detection of breast cancer. Firstly, methods of pre-processing the image are looked at. This is to make the images suitable for the next phase of breast cancer detection. Two techniques of edge detection are chosen to be implemented as investigation for the use for early breast cancer detection. One of them is the simple Sobel edge detector and the other is the computationally more intensive Shen-Castan edge detector. After the image is processed by a detector, post-processing techniques are used to improve the presentation of the results.